2018
DOI: 10.1177/1708538118809854
|View full text |Cite
|
Sign up to set email alerts
|

Vascular surgery: What increases the flow of students to the speciality?

Abstract: Objectives Vascular surgery is in increasing demand due to the higher prevalence of cardiovascular disease in the general population. Meanwhile, applications to join the speciality have been in decline in the last few years. St George’s Surgical Society held a one-day conference to expose undergraduates to the speciality in the hope that this will inspire more undergraduates to pursue it as a career. Methods The conference consisted of introductory lectures delivered by a consultant vascular surgeon, followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
1
6
0
4
Order By: Relevance
“…To the authors knowledge there are currently no UK based studies focusing on medical student perspectives on orthopaedics or how these perspectives might be altered. One small UK study investigating factors increasing the flow of students to vascular surgery found a one day student surgical society conference attended by 36 students, resulted in a 18% decrease in the negative perception that vascular surgery is female-unfriendly and 33% increase in interest in vascular surgery ( 25 ). However, the gender of respondents was not available making these results hard to interpret in the context of improving female representation.…”
Section: Discussionmentioning
confidence: 99%
“…To the authors knowledge there are currently no UK based studies focusing on medical student perspectives on orthopaedics or how these perspectives might be altered. One small UK study investigating factors increasing the flow of students to vascular surgery found a one day student surgical society conference attended by 36 students, resulted in a 18% decrease in the negative perception that vascular surgery is female-unfriendly and 33% increase in interest in vascular surgery ( 25 ). However, the gender of respondents was not available making these results hard to interpret in the context of improving female representation.…”
Section: Discussionmentioning
confidence: 99%
“…La especialidad de angiología y cirugía vascular durante los estudios de Medicina posee un peso pequeño dentro de los programas de las diferentes facultades, lo que provoca que sea prácticamente desconocida para muchos de ellos. Esta diferencia entre la prevalencia de las enfermedades que trata la angiología y la cirugía vascular y el conocimiento básico impartido a los estudiantes de Medicina también se presenta en otros países de nuestro entorno (6). Así, en el Reino Unido también ha disminuido en los últimos años el interés por realizar la especialidad de vascular (7).…”
Section: ¿Es Atractivo Ser Angiólogo Y Cirujano Vascular En 2020?unclassified
“…Este último parece ser el principal factor para la elección en la mayoría de los médicos que escogen la especialidad. La literatura apoya este concepto, y concluye que el principal determinante en la elección de la especialidad de cirugía vascular es haber estado "expuesto" durante la carrera de Medicina (6).…”
Section: ¿Es Atractivo Ser Angiólogo Y Cirujano Vascular En 2020?unclassified
See 2 more Smart Citations